The incorporation of Chia seeds (Salvia hispanica L.) in the chicken diet promotes the enrichment of meat with n-3 fatty acids, particularly EPA and DHA - Ayrton da Silva; María Cristina Cabrera; Roberto Olivero; Marta del Puerto; Alejandra Terevinto; Ali Saadoun (Applied Food Research, 2024)
Chia seeds, an ancestral food produced in South America, have been utilized to supplement the diet of chickens with the objective of increasing the meat content of n-3 fatty acids. Chia seeds are notably rich in α-linolenic acid, an essential fatty acid comprising 62% of the total fatty acids in chia. The expectation was that feeding chickens with such a level of α-linolenic acid would promote its conversion to EPA, DPA, and primarily DHA, considering the favorable impact of these fatty acids on consumer health. To achieve this goal, 96 male Ross chickens were provided ad libitum diets supplemented with 0%, 2.5%, 5%, and 10% of chia seeds. At 49 days of age, the animals were slaughtered, and the Gastrocnemius, Iliotibialis lateralis, and Pectoralis major muscles were analyzed. The results indicated that chia seeds did not have a negative impact on the productive parameters. Regarding meat color, the inclusion of chia in the feed appeared to lower the redness of meat, especially in Pectoralis major, without apparent effects on the pHu neither for the drip loss of the meat. Chia seeds led to an increased deposition of C18:3n3, EPA, DPA, and DHA into the muscles. The DHA levels detected in the muscles in our study could be considered relatively high when compared to the findings of other investigations using chia seeds in chickens, especially given the extent of chia seed incorporation in the feed. On the other hand, meat indices such as total n-3 fatty acids, n-6/n-3 ratio, AI (atherogenicity), TI (thrombogenicity), and h/H (hypocholesterolemic effect) are favorable for consumers' health when chia seeds are included in the feed of chickens, except for AI and h/H when chia is included at 10% in the feed.